Bamboo Flute Music Development in Timor Tengah Utara Community in The Context of Social Changes - Mau, Laurensius Yosef; Wadiyo, Wadiyo; Sunarto, Sunarto (Catharsis, 2021)
Bamboo flute music is a typical traditional music of Timor Tengah Utara (TTU). It was one of the most favourable traditional arts and shown at various events, such as religious events, local government events even as a welcoming music for the country guests. As the time goes by, the existence of bamboo flute music currently has been declined and it was because of various factors, one of it was the social and cultural changes of the community which influenced the development of bamboo flute music. The method used in this research was analytical qualitative method. The data collection techniques used observation, interview, and document study. The technique of data validity used sources triangulation. The data analysis in this research used social changes theory. Based on the results of this research, it can be found that the development of bamboo flute music is influenced by the changes in cultural elements which are the knowledge system that evolves over the time; the livelihood system that the majority of the community back then was as farmers and now turn into office employees; the technology system that is the current rapid development and advanced technology information which impacts on the technology effectiveness and eficiency towards the community life; as well as the art elements that continue to develop according to the needs and trend. This research expands the perspetive of the readers about the existence and influene of cultural elements changes towards the development of bamboo flute music in Timor Tengah Utara (TTU) Regency.